H. Darin Drabkin. Land policy and urban growth. Oxford : Pergamon Press, 1977. 444 p. - Schteingart, Martha (Estudios Demográficos y Urbanos, 1979)
H. Darin Drabkin, Land Policy and Urban Growth, Oxford, Pergamon Press, 1977.